Ethanol Augments PDGF-Induced NADPH Oxidase Activity and Proliferation in Rat Pancreatic Stellate Cells - Hu, Richard (S. Karger AG, 2007)
BACKGROUND/AIMS: Activated stellate cells are considered the principal mediators of chronic alcoholic pancreatitis/fibrosis. However the mechanisms of alcohol action on pancreatic stellate cells (PaSCs) are poorly understood. The aims of this study were to determine the presence and role of the NADPH oxidase system in mediating alcohol effects on PaSCs with specific emphasis on proliferation. METHODS: PaSC NADPH oxidase components mRNA and protein were determined by RT-PCR and Western blot. The NADPH oxidase activity was measured by detecting the production of reactive oxygen species using lucigenin-derived chemiluminescence assay. PaSC DNA synthesis, a measure of proliferation, was performed by determining the [(3)H] thymidine incorporation into DNA. RESULTS: mRNA for NADPH oxidase components Nox1, gp91(phox), Nox4, p22(phox), p47(phox) and p67(phox) and protein for NADPH oxidase subunits gp91(phox), p22(phox), p47(phox) and p67(phox) are present in PaSCs. Treatment with platelet-derived growth factor (PDGF) significantly increased the NADPH oxidase activity and DNA synthesis in cultured PaSCs. Alcohol treatment markedly augmented both the NADPH oxidase activity and the DNA synthesis caused by PDGF, which was prevented by antioxidant N-acetyl-L-cysteine, ROS scavenger tiron, and the NADPH oxidase inhibitor diphenylene iodium. The effects of PDGF on NADPH oxidase activity and DNA synthesis were prevented in PaSCs isolated from the pancreas of mice with a genetic deficiency of p47(phox). CONCLUSIONS: Ethanol causes proliferation of stellate cells by augmenting the activation of the cell's NADPH oxidase system stimulated by PDGF. These results provide new insights into the mechanisms of alcohol-induced fibrosing disorders.